COVID-19 in Egypt: Impacts on Production, Household Income & Food Systems - Breisinger, Clemens; Raouf, Mariam; Wiebelt, Manfred; Kamaly, Ahmed; Karara, Mouchera (2021)
Prepared by Clemens Breisinger1, Mariam Raouf1, Manfred Wiebelt2, Ahmed Kamaly3, Mouchera Karara3 1. International Food Policy Research Institute 2. Kiel Institute for the World Economy